Persepsi Mahasiswa terhadap Sebuah Video Pendek Berjudul Diskriminasi Gender - Dina Chunaifi Ubaidillah; Tri Wahyono; Naufal Daffa Adibta (Jurnal Hukum, Administrasi Publik dan Negara, 2024)
This research aims to explore students' perceptions of a short video entitled "Gender Discrimination". This video was created to convey messages regarding issues of gender discrimination that individuals may face in everyday life. The research method used is a qualitative study by conducting in-depth interviews with a number of students representing various backgrounds and views. The research results show variations in students' perceptions of the messages conveyed in the video, as well as how this video influences their understanding of the issue of gender discrimination.